2021
DOI: 10.3390/nu13093202
|View full text |Cite
|
Sign up to set email alerts
|

Ketogenic Diets in Pancreatic Cancer and Associated Cachexia: Cellular Mechanisms and Clinical Perspectives

Abstract: Pancreatic ductal adenocarcinoma (PDAC) is an aggressive and extremely therapy-resistant cancer. It is estimated that up to 80% of PDAC patients present with cachexia, a multifactorial disorder characterized by the involuntary and ongoing wasting of skeletal muscle that affects therapeutic response and survival. During the last decade, there has been an increased interest in exploring dietary interventions to complement the treatment of PDAC and associated cachexia. Ketogenic diets (KDs) have gained attention … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 154 publications
0
14
0
Order By: Relevance
“…The ketogenic diet has been suggested as a treatment for a wide range of medical conditions, including migraines (17), epilepsy (18), multiple sclerosis ( 19), Alzheimer's disease (20), diabetes (21), aging (22), cancer (23), and cancer associated cachexia (24). One of the primary mechanisms underlying the purported benefits of the ketogenic diet is the switch from glucose as a primary fuel to fatty acids and ketone bodies.…”
Section: Discussionmentioning
confidence: 99%
“…The ketogenic diet has been suggested as a treatment for a wide range of medical conditions, including migraines (17), epilepsy (18), multiple sclerosis ( 19), Alzheimer's disease (20), diabetes (21), aging (22), cancer (23), and cancer associated cachexia (24). One of the primary mechanisms underlying the purported benefits of the ketogenic diet is the switch from glucose as a primary fuel to fatty acids and ketone bodies.…”
Section: Discussionmentioning
confidence: 99%
“…Pancreatic cancer is one of the malignant tumors of the digestive system with the highest mortality, accounting for the fourth place in the cancer-related mortality [ 1 , 2 ]. In recent years, epidemiology has found that the number of new pancreatic cancer cases in both male and female is increasing [ 3 , 4 ]. In the USA, the number of new malignant tumors ranks 10th in men and 9th in women among all tumors [ 5 ], and in China, the number ranks 7th in men and 11th in women [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Multiple cellular mechanisms might explain the beneficial effects of a KD in tumor growth. These include anti-inflammatory, anti-angiogenesis, cell metabolism and epigenetic effects, as well as modulation of the microbiome (15). Unfortunately, many of these studies were performed using xenograft models of pancreatic cancer, which do not closely recapitulate human PDAC, so their clinical significance are limited (16).…”
Section: Introductionmentioning
confidence: 99%